Design and development of an automated magnetic particle testing of automotive parts. - Hrairi, Meftah ([s.n], 2012)
An automated system for magnetic particle inspection has been developed in this research for the nondestructive testing industry. The automation hardware was designed and developed in conjunction with a machine vision system. A control valve was introduced for the application of magnetic particles during inspection. A DC motor was used to orient the tested specimen under the camera vision range. The specimen is then inspected for certain type of defects. A C++ program was developed to perform image processing and the automation of the hardware. A microcontroller was used to send commands to the hardware from the programmed software. The automation hardware and software were integrated to enhance the existing magnetic particle inspection machine.